SLIP BEADING TECHNIQUE TREATMENT IN THE PROCESS OF MAKING OXFORD SHOES - Abimanyu Yogadita R; Sanjaya Nugraha; Warsito (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2023)
Slip beading is an edge treatment that is commonly carried out by the sports shoe industry. Slip beading is a treatment on the edges that can add to the appearance of shoes to be more aesthetic. Slip beading is actually very good even though the work is difficult because the ribbon for the slip beading can use a different color from the color of the top of the shoe, but by being clever in choosing the color you will get shoes with a good appearance and contrasting color variations. Difficulties in the application of variations of slip beading arise due to the thickness of the material and it is only possible to do it with sophisticated equipment. Based on these problems, it is necessary to conduct research on the application of slip beading variations on shoes with classic models. The method used in this research is a qualitative method with an experimental method. That is trying to test with several samples of size variations in slip beading and several materials to find the best composition of size variations and material variations. The results of this study are the emergence of oxford shoe designs with variations of slip beading that match the material and width of the shoe components.